2023
DOI: 10.56801/seejph.vi.155
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and perception about climate change among healthcare professionals and students: A cross-sectional study

Abstract: Aim: The aim of this study was to assess knowledge on Climate Change (CC) and related consequences among students and professionals of healthcare setting. Methods: A cross-sectional study involving 364 people was conducted. The survey was performed at Sapienza University (Rome) using questionnaire previously developed and validated by the same research group. Results: Findings indicate awareness about CC and its effects and correct identification of practices that could help to mitigate its repercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…The results showed that the nursing students have a good grasp or understanding of what climate is and its main causative factor. This finding is consistent with previous studies conducted abroad among nurses and other healthcare professionals (Anåker et al, 2015;Hathaway & Maibach, 2018;La Torre et al, 2020). Similarly, it corresponds with previous studies conducted among nursing students abroad, indicating adequate knowledge and understanding of climate change (Felicilda-Reynaldo et al, 2018;La Torre et al, 2020;Yang et al, 2018).…”
Section: Nursing Students' Understanding Of Climate Changesupporting
confidence: 92%
See 2 more Smart Citations
“…The results showed that the nursing students have a good grasp or understanding of what climate is and its main causative factor. This finding is consistent with previous studies conducted abroad among nurses and other healthcare professionals (Anåker et al, 2015;Hathaway & Maibach, 2018;La Torre et al, 2020). Similarly, it corresponds with previous studies conducted among nursing students abroad, indicating adequate knowledge and understanding of climate change (Felicilda-Reynaldo et al, 2018;La Torre et al, 2020;Yang et al, 2018).…”
Section: Nursing Students' Understanding Of Climate Changesupporting
confidence: 92%
“…Allied health students were found to have moderate to good level of knowledge and awareness about what climate change is and its negative effects on human health (Felicilda-Reynaldo et al, 2018;La Torre et al, 2020;Liao et al, 2019;Opoku et al, 2021;Yang et al, 2018). Nursing students were also found to be knowledgeable about climate change and that it negatively affects human health (Felicilda-Reynaldo et al, 2018;La Torre et al, 2020;Yang et al, 2018). However, nursing students have a lower level of knowledge and awareness of the effects of climate change on health compared to medical students (Liao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2022 survey of Italian pediatric pulmonologists found that the overwhelming majority of participants were interested in the issue of climate change and health (96%) and more than three out of four agreed that it is the "greatest global health threat of the 21st century" (76%; Lauletta et al, 2022). Another recent study conducted among health professionals in Italy demonstrated that a significant majority (97%) acknowledged the potential impact of global warming on human health and recognized (93%) the capacity of health professionals to contribute towards reducing these impacts (Torre et al, 2023). A survey of a global gastroenterology society's leadership found that most participants (86%) believed that climate change was human-caused, although many also believed there were more pressing issues for their societies to attend to (80%; Leddin et al, 2022).…”
Section: Image Credit: Climate Visualsmentioning
confidence: 99%
“…Over 100 million individuals could be affected negatively by the effects on population health globally by 2030. Additionally, it is predicted that developing nations will be the most severely impacted because of their disproportionate exposure as well as their less-developed infrastructure and health systems (Torre et al, 2020). Rising sea levels, an increase in the spread of infectious diseases, food and water shortage, political unrest, mass migration and loss of finances are all consequences of climate change that negatively impact people's physical, mental, and social well-being (Álvarez et al, 2022).…”
Section: Introductionmentioning
confidence: 99%